Does Race Matter? - Outcomes of the First Year Experience in a Canadian University - Grayson, J. Paul (Canadian Journal of Higher Education, 1995)
Canadian cities are experiencing increasing ethnic and racial diversity. As a result there is a growing concern with the degree to which Canadian institutions meet the needs of a heterogeneous population. Despite this concern, as yet, there have been no systematic studies of race relations on Canadian campuses and the degree to which outcomes of the university experience are affected by race. Data for the current study were collected at York University through a survey of 1,093 students at the time of entry in September and a survey of 1,129 students conducted in February/March of the first year. Data analysis focuses on the background characteristics of students of various races, their social and academic involvement and classroom experiences, outcomes of the first year in university, and the degree to which race affects both experiences and outcomes. It is found that in general students of non-European origins come from families with different socio-economic characteristics than those of European descent. In addition, the nature of the university experience varies by minority status and/or race. Comparisons, however, do not always favour students of European origin. Finally, although some outcomes of the first year experience - self-assessed intellectual development and knowledge, grade point averages, and intentions to return to the university - vary by racial group; race per se explains little, if any, of the total variance. In essence, there is a considerable degree of equality in outcomes so far as race is concerned. Explanations for differences in outcomes are to be found in classroom experiences, contacts with faculty etc., and academic involvement.